Objeto de aprendizagem na forma de game como auxílio ao professor na promoção do ensino - Lima, Rubens Renato da Silva de (2019)
This research aimed to analyze how the use of a learning object in the form of game can contribute to the processes of teaching mathematics. The participants were four teachers and their high school classes from schools in Porto Alegre - RS and metropolitan region, two private schools and two public schools. As a data collection instrument, two questionnaires were applied one before the teachers applied the game in their classes and the other after the application of the game. The other instrument that was used as data collection for the research were the descriptions of the observations made by the researcher in each workshop applied by the teachers. The responses to the two questionnaires and the content of the observations were analyzed in a qualitative way using the method created by Moraes and Galiazzi Textual Discursive Analysis- ATD. Using the analysis technique defined by the ATD emerged three categories and subcategories. In the Game category and its Contribution to students 'teaching, participants' perceptions about the use of the game as an activity to engage and stimulate students in the creation of strategies in practice, the game as an instrument that can be used for the introduction of content, review and resume, as well as a tool that allows students to reflect on the error. The Game category as Teacher Teaching Practice evidenced the use of the game as a play activity that, in addition, allows to review the contents that were seen, making the teacher need to play a role of mediator of the teaching with the use of the game. And the third category The Game navigation format and Efficient Learning brings the importance of the order of difficulty in educational games and that the structure of free navigation in games, although more freedom for students to linear is more challenging. It is concluded that the use of a game can be a viable alternative for teachers to use in their teaching practices as a playful alternative that allows reviewing the content, stimulating the creation of strategies in a practical way and that the form of linear navigation ends up being more challenging for students.